Personal Marketing Strategies of Online Game Streamers - Mendoza, Xavier Lawrence Dela Rea; Tadeo, Jerico B.; Dela Cruz, Monica A.; Gonzales, Denmark Cris A.; Pamintuan, Roselle Q. (International Journal of Computing Sciences Research, 2023)
Purpose – The study aimed to evaluate the personal marketing strategies of online game streamers in the selected areas of Cavite Province, Philippines. Method – This study utilized a descriptive research design to describe the variables understudy and a correlational research design to identify the significant relationship between the demographic profile of the respondents and the perceived effectiveness of personal marketing strategies. A purposive sampling technique was utilized to collect responses from 80 online game streamers. Results –   The study found that the level of perceived effectiveness of the personal marketing strategies of online game streamers was highly effective. There was no significant relationship between the respondents’ demographic profile and the level of perceived effectiveness of personal marketing strategies. Conclusion – The researchers found that personal marketing strategies were employed and highly effective upon their respective implementation. Recommendations – The researchers recommend that online game streamers must first determine their needs in terms of their resources, capital or income, and preferences before deciding on what personal marketing strategies they will apply in the streams.  Research Implications – The study looks forward to enhancing online gaming streamers' personal marketing strategies by incorporating localized strategies that could address their respective environments to have more targeted, specific, and focused personal marketing strategies.